A systematic review of migrants’ non-employment precarity–conceptualizations by scholars and migrants’ narratives - Suet Lin Hung; Chi Yuen Lai; Kwok Kin Fung (Comparative Migration Studies)
Abstract Precarity is a term capturing the migrants’ situation under globalization and migration-driven uncertainties. Many have attempted to explain the precarity in terms of employment changes, but fewer in terms of non-employment ones. A systematic review is conducted to summarize the conceptualization of migrant precarity manifested in non-employment aspects. Studies (n = 46) from 2014 to 2024 were selected by searching through social science databases of using the keyterms of “precarity” or “precarization” or “precariat” or “precariousness” AND “migrants” or “migration”. Precarity conceptualizations were compared by migrants’ narratives to identify precarity items omitted in literature. Findings showed that migrants’ precarities suffer from typical economic, social and legal precarities. Yet, precarities of household, information and housing are understudied. Moreover, analyzation of migrants’ narratives shown mismatches to scholar’s conceptualization, which reflects a need for scholars to research with the voices of migrants to rectify the conceptualization. The review also shows a socially reproduction relationship between precarities, while multidimensional conceptualizations will help scholars’ analysis to stick consistently to migrants’ experiences. It is also recommended to research more on information, housing, and psychological precarity, apart from a need to adopt longitudinal lens into migrant precarity studies. Words count for body of manuscript: 8,524 (excluding references and appendix).